Myth as Revelation - Miller, Robert (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2014)
This essay explores how myth functions as a means of revelation in Scripture. It first clarifies a definition of myth, and then discusses the appearance of myth in the Old Testament. Not only is myth found in the Bible, but its presence is of great importance. Considering the various functions of myths in general, it becomes indispensable that myth form a part of the inspired canon. Revelatory myth is essential, especially today. Finally, this essay considers how one might recapture an appreciative reception of biblical myths.